The China-Australia Free Trade Agreement (ChAFTA): its implications for Australia-United States relations - Johni Robert Verianto Korwa (Parahyangan Center for International Studies, 2019)
Australia is currently faced with a strategic and economic dilemma regarding its interactions with China and the United States (US). On the one hand, it should maintain and strengthen its strategic relations with the US as an ally in order to contain a rising China. On the other hand, Australia should ensure its economic growth by strengthening trade relations with China. This paper aims to examine the implications of the new China-Australia Free Trade Agreement (ChAFTA) for the ANZUS strategic alliance. Through Qualitative Approach, this article analyzes the issues with the use of realist and liberal perspectives in international relations. By assessing two previous events involving the triangular Australia-US-China relationship (the case of the Taiwan conflict, and the US development of a National Missile Defense system), this paper concludes that ChAFTA may tend to undermine the ANZUS alliance. Three reasons for this conclusion are identified: a fundamental shift in the way Australia perceives China; ChAFTA offers more benefits to Australia than the Australia-US Free Trade Agreement (AUSFTA); and finally Australia may consider ChAFTA as being more in its national interests in the international system than the ANZUS alliance.